Advances in Fluid Mechanics IX 2012
DOI: 10.2495/afm120211
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the CFD model for prediction of flow behaviour in fluidized bed reactors

Abstract: The aim of this study is to develop a robust CFD model for predicting fluid dynamics in a gasification reactor. Experimental tests are performed. A cylindrical bed with pressure sensors is used in the experimental study. A series of simulations are performed using the commercial CFD tool ANSYS Fluent 12.1. A multi-fluid Eulerian model incorporating the kinetic theory of granular flow is applied in the simulations. Fluidized bed reactors in biomass gasification processes use steam as a fluidizing gas. High temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A good agreement between the experimental measurements and the model predictions were established. The details of the validation work performed by the authors can be found in WIT Transactions on Engineering Series 2012 [13].…”
Section: Viscous Limit Set Of Scaling Rulesmentioning
confidence: 99%
“…A good agreement between the experimental measurements and the model predictions were established. The details of the validation work performed by the authors can be found in WIT Transactions on Engineering Series 2012 [13].…”
Section: Viscous Limit Set Of Scaling Rulesmentioning
confidence: 99%